Improving The Methodology Of Teaching Biophysics To Students Of Higher Agricultural Education - Sherkuziyev Mamadiyar; Khudayarov Makhmasaid; Abdinazarov Akbar (American Journal of Botany and Bioengineering, 2026)
The goal of this project is to enhance the way that students in higher agricultural education are taught biophysics. The study emphasizes how crucial it is to use cutting-edge teaching strategies, interdisciplinary links, and contemporary pedagogical approaches to improve students’ comprehension of biophysical processes in agricultural systems. Information and communication technology, engaging instructional methods, and useful applications pertaining to actual agricultural issues are all given special consideration. The suggested methodological changes are intended to enhance students’ capacity for independent learning, professional competencies, and critical thinking. Additionally, the study highlights how biophysics plays a crucial role in developing agricultural science and practice by providing an explanation of biological processes at the molecular and cellular levels. The findings of this study may help improve the caliber and efficacy of biophysics instruction in higher agricultural establishments. The study examines current conventional teaching approaches and points out their shortcomings, including low student involvement, a lack of practical emphasis, and inadequate integration with professional agriculture courses. In response, the study suggests a number of methodological enhancements based on student-centered, competency-based, and problem-based learning strategies. The use of interactive teaching techniques, such as case studies, project-based learning, simulation models, and experimental laboratory work specific to agricultural contexts such soil dynamics, plant physiology, water balance, and energy exchange, is given particular attention.